Comparative Bone Density Studies in Mammals (Zoological Archives: An International Journal, 2026)
Bone density -- quantified as bone mineral density (BMD) and bone volume fraction (BV/TV) -- varies substantially acrossmammalian taxa in relation to body mass, locomotor mode, diet, and phylogenetic affinity, reflecting the biomechanicaldemands of diverse ecological niches. This study conducted the most comprehensive comparative analysis ofmammalian bone density to date, quantifying BMD (dual-energy X-ray absorptiometry, DXA) and trabecularmicroarchitecture (microCT; 14 structural parameters) from 1,284 femur and lumbar vertebra specimens representing 84species across 14 mammalian orders from eight European natural history collections. Body mass explained 68.4% ofvariance in cortical bone thickness (allometric slope = 0.38 +/- 0.02 on log-log axes), while locomotor category explainedan additional 18.4% of variance after controlling for body mass (semi-aquatic species showing densest bone, fossorialspecies intermediate, cursorial lowest for equivalent mass; F3,76 = 28.4, p < 0.001). Trabecular bone volume fraction(BV/TV) was highest in compression-loaded vertebrae of heavy semi-aquatic mammals (mean 42.4 +/- 6.4%) and lowestin long bones of small arboreal mammals (mean 12.4 +/- 3.2%). Phylogenetically controlled regression confirmedlocomotor mode as an independent predictor of bone density beyond body mass and diet (PGLS partial r = 0.62, p